2020
DOI: 10.1038/s41433-020-0769-4
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal follow-up of dome-shaped macula

Abstract: Background/objectives To determine if the presence of sub-retinal fluid (SRF) was associated with reduced vision in dome-shaped macula (DSM), and to assess its effect and response to treatment during follow-up. Methods Patients were identified retrospectively. Baseline and follow-up data were recorded. The diagnosis of DSM, and presence or absence of SRF and intra-retinal fluid (IRF) was confirmed using Spectral Domain-Optical Coherence Tomography (SD-OCT). Decisions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…4,5 In this study, we included five eyes with DSM smaller than 50 µm. As this limit has been proposed in many studies to consider the presence of DSM, 7, [11][12][13][14][15] one may argue that those eyes may have biased the results of the present work. Indeed, to exclude this possibility, we performed the statistical analysis after exclusion of those five eyes.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…4,5 In this study, we included five eyes with DSM smaller than 50 µm. As this limit has been proposed in many studies to consider the presence of DSM, 7, [11][12][13][14][15] one may argue that those eyes may have biased the results of the present work. Indeed, to exclude this possibility, we performed the statistical analysis after exclusion of those five eyes.…”
Section: Discussionmentioning
confidence: 87%
“…Considering that DSM has been previously reported in emmetropic and hyperopic eyes, 5 the emmetropic or hyperopic state and the absence of posterior staphyloma were not considered as exclusion criteria. In the literature, some studies have excluded DSM inferior to 50 µm, 7, [11][12][13][14][15] while some other did not. 1,[4][5][6]8 In the present work, the DSM height inferior to 50 µm was not an exclusion criterion.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…225 The fluid resolution may also correspond with the development of RPE and outer retina atrophy in the macula. 219 Most studies of SRF associated with dome-shaped macula have shown a poorer visual acuity at baseline or during the follow-up 219,226 but in one study, a similar prognosis has been reported between eyes with and without SRF after a 2-year follow-up. 227 Other reported complications include pigment epithelial detachment at the dome apex, 228 polypoidal choroidal vasculopathy, 229 and MNV that is more easily detected on OCTA.…”
Section: Dome-shaped Maculamentioning
confidence: 89%
“…Although the prevalence of DSM has not been reported by any population-based study, incidence of DSM in highly myopic eyes has been estimated as 20% in Japan [13], 16% in Turkey [14], and 11% in Europe [15]. DSM has been documented in adults, adolescents, and children in many other parts of the world, namely, Canada [11], USA [16,17], UK [18,19], Europe [10,15,20,21], Korea [22,23], and Japan [16,24]. Although, DSM was initially believed to occur exclusively in high myopic eyes with staphyloma, it has also been described in emmetropes, hypermetropes [18], and eyes without staphyloma [16].…”
Section: Introductionmentioning
confidence: 99%